The versatility of polymeric materials as self-healing agents for various types of applications: A review - Kahar N.N.F.N.M.N.; Osman A.F.; Alosime E.; Arsat N.; Azman N.A.M.; Syamsir A.; Itam Z.; Hamid Z.A.A. (MDPI AG, 2023)
Functional polymers; Self-healing materials; Construction fields; External stimulus; Extrinsic mechanisms; Healing agents; Intrinsic mechanisms; Self healing mechanism; Structure failure; Vascular network; Failure (mechanical)